The Humanism Values in Paulo Coelho's Brida - Pingge, Marlin; Pramesti, Tri (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
The study analyzes human values in Brida by Paulo Coelho (1990). The objectives of the study are aimed to describe the process of discovering human values. This study uses systemic humanism theory by Abraham Mashlow. In relation to humanism, the study approach uses a humanism approach. This study also uses qualitive research to examinemore deeply the forms of humanism values that are described in the form of novel. a context analysis approach also used to understand the correlation between literature and the values of humanism in the novel. The analysis of the study shows that humanism is the whole of life, which in this novel is explained throuhg and ideal of life and the process of achieving that ideal. The main character in tha novel is a girl who is looking for her identity through several test to persue her dream of becoming a witch. Based on the story of the character, this analysis find that ideals provide the meaning of human being and ideal existence, which then means as humanism. The values of humanism contained in the characters namely hope,love, suffering, and happiness. The value of character humanism also appears in every process it goes through, such as attitude, sacrifice, self - control, rationality, commitment, and self-confidence